The Recent Financial Turmoil : Initial Assessment, Policy Lessons, and Implications for Fund Surveillance. (Policy Papers; Policy Paper, 2008)
In response to the IMFC's October 2007 communique, IMF staff has sought to assess the causes of the present turbulence and draw tentative lessons in order to inform its future bilateral and multilateral surveillance work. This effort has involved close collaboration with the Financial Stability Forum (FSF) and its working groups, as well as consultation with the private sector, national authorities, standard setters, and other bodies.